Effects of maternal history of depression and early life maltreatment on children's health-related quality of life - Dittrich, Katja; Fuchs, Anna; Reichl, Corinna; Kaess, Michael; Möhler, Eva; Zietlow, Anna-Lena; Herpertz, Sabine; Brunner, Romuald; Resch, Franz (Journal of affective disorders, 2017)
Background: There is a well-established link between maternal depression and child mental health. Similar effects have been found for maternal history of early life maltreatment (ELM). However, studies investigating the relationship of children's quality of life and maternal depression are scarce and none have been conducted for the association with maternal ELM. The aim of the present study was to investigate the effects of maternal history of ELM and depression on children's health-related quality of life and to identify mediating factors accounting for these effects. Methods Our study involved 194 mothers with and without history of depression and/or ELM and their children between five and 12 years. Children's health-related quality of life was assessed by maternal proxy- and child self-ratings using the KIDSCREEN. We considered maternal sensitivity and maternal parenting stress as potential mediators. Results: We found an effect of maternal history of depression but not of maternal history of ELM on health-related quality of life. Maternal stress and sensitivity mediated the effects of maternal depression on child global health-related quality of life, as well as on the dimensions Autonomy & Parent Relation, School Environment (maternal and child rating), and Physical Wellbeing (child rating). Limitation: Due to the cross-sectional design of the study, causal interpretations must be made with caution. Some scales yielded low internal consistency. Conclusions: Maternal impairments in areas of parenting which possibly developed during acute depression persist even after remission of acute affective symptoms. Interventions should target parenting stress and sensitivity in parents with prior depression.
Gesehen am 25.04.2018